Social Networks Seminar - Friedkin, Noah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The purpose of this seminar is to explore and discuss the frontier of substantive (non-methodological) research on social networks in Sociology, where this frontier is manifested in articles that have appeared in mainstream sociological journals. Since orientation of the course is substantive, we will not be spending much time on the methodological foundations of the findings presented in the articles. Our discussion will focus on the research problem of the article, the findings, the conclusions, and how social networks entered into the analysis and thinking of the author(s).